Case report: ex vivo tumor organoid drug testing identifies therapeutic options for stage IV ovarian carcinoma - Al-Aloosi, Marwah; Prechtl, Amanda M.; Chatterjee, Payel; Bernard, Brady; Kemp, Christopher J.; Rosati, Rachele; Diaz, Robert L.; Appleyard, Lauren R.; Pereira, Shalini; Rajewski, Alex; McDonald, Amber; Gordon, Eva J.; et al. (Frontiers in Oncology, 2024)
Patients presenting with stage 4 ovarian carcinoma, including low grade serous disease, have poor prognosis. Although platinum-based therapies can offer some response, these therapies are associated with many side effects and treatment resistance often develops. Toxic side effects along with disease progression render patients unable to receive additional lines of treatment and limit their options to hospice or palliative care. In this case report, we describe a patient with an unusual case of metastatic low grade serous ovarian cancer with some features of high-grade disease who had received four previous lines of treatment and was suffering from atelectasis, pulmonary embolism, and hydronephrosis. A CLIA certified drug sensitivity assay of an organoid culture derived from the patient's tumor (PARIS  test) identified several therapeutic options including the combination of fulvestrant with everolimus. On this treatment regimen, the patient experienced 7 months of stable disease and survived nearly 11 months before succumbing to her disease. This case emphasizes the clinical utility of ex vivo drug testing as a new functional precision medicine approach to identify, in real time, personalized treatment options for patients, especially those who are not benefiting from standard of care treatments.